THE ECONOMIC COMPETITION BETWEEN UNITED STATES, EUROPEAN UNION AND CHINA - Ștefan Cătălin TOPLICEANU (Challenges of the Knowledge Society, 2019)
The economic and political developments at the end of the 20th century, but especially those at the beginning of the 21st century, have led to numerous debates, analyze and forecasts on international power structures. Various debated events, such as economic, social and political crises of multiple magnitudes, military-ideological conflicts in different areas of the world, migration flows and socio-cultural transformations, have announced new phenomena regarding power centers of the world economy. Under the impact of these international events, there is often discuss about the decline of American supremacy, European economic reformation and the rise of emerging economies, especially China. Related to these developments, different models of power structures are emerging, in which countries and groups (especially the United States, the European Union and China) rotate among themselves in the hope of designing a system of world power. Among all the nuances of power, the most important component remains economic power, being the decisive element of the development of other types. For this reason, in the world power relations, a clear picture of the existing power structures is needed. This study aims to analyze the economic competition and the power hierarchy between the United States, the European Union and China.